Left main bronchus compression as a result of tuberculous lymphnode compression of the right‐sided airways with right lung volume loss in children. Issue 3 (28th November 2012) - Andronikou, S.; Van Wyk, M.J.; Goussard, P.; Gie, R.P.
Abstract Rationale The superior mediastinal space is confined by the sterno‐manubrium anteriorly and the vertebral column posterior. An abnormal relationship between the superior mediastinal structures may result in compression of the left main bronchus. In patients with right‐sided pneumonectomy an exaggerated compensatory response may lead to stretching and compression of the remainder of the intra‐thoracic airway. Lymphobronchial TB mimics pneumonectomy when it causes compression of the bronchus intermedius, between nodal lymphnode groups with resultant volume loss in the right lung and displacement of the mediastinum to the right. The left main bronchus may be at risk of compression due to rotation and displacement of the major vessels. Aim To report pediatric cases of right‐sided lymphobronchial TB with volume loss, demonstrate the use of angle measurements to quantify mediastinal dynamics and support a pathogenetic theory for left main bronchus compression. Materials and Methods CT scans in children with TB and right lung volume loss, were compared retrospectively with controls using angle measurements based on descriptions of the aorta‐carinal syndrome and the post‐pneumonectomy syndrome. The Mann–Whitney U‐test was used to compare groups. Results The "Pulmonary bifurcation angle" between the main pulmonary arteries reached statistical significance (P = 0.025). The "Pulmonary outflow tract rotation" angle (pulmonary trunk with the mid sagittal plane) approached statistical significance (P = 0.078). The left main bronchus ranged from complete obliteration in two patients to 0.7 cm. In 16 of 30 patients the size was reduced to less than 75% of expected. Conclusion In children with right lung volume loss from TB, the compression of the contralateral bronchus is due to narrowing of the pulmonary artery bifurcation angle as the main trunk rotates towards the midline. This is comparable to the post‐pneumonectomy syndrome. Pediatr Pulmonol. 2014; 49:263–268. © 2012 Wiley Periodicals, Inc.